PERANCANGAN SISTEM INFORMASI GEOGRAFIS PEMETAAN DAERAH RAWAN TANAH LONGSOR, MITIGASI DAN MANAJEMEN BENCANA DI KABUPATEN BANJARNEGARA - Setiadi, Tedy (Universitas Ahmad Dahlan, 2013)
ABSTRAKBackground: Banjarnegara district is an area prone to landslides. Current disaster management system landslide is not yet available, while for mapping landslide area already exists, but in the form of a conventional map. As a result, the information is static, difficult updated and does not provide a lot of information that people need because it is not accessible by the public.Metode yangMethods : Using sequential linear methods (waterfall) include systems analysis and design stages of the system. In the analysis of the classification system is to determine user needs and specifications. In system design includes the design DFD to model the process, ERD to model the data, as well as interface design (prototype).Results :This research yield the system requirements specification, design and prototyping process DFD. The features of which include mapping of landslide-prone areas, mitigation and disaster management. System is equipped with an early warning activitiesto deliver information in the form of results predicted weather/climate. While the disaster management system in the form of the ability to display the number of refugees, the number of refugee shelters, layout-layout and post evacuation needs of each postÂ Keywords : GIS, Landslides, Mitigation, Disaster Management